الحياة الأدبية في بجاية من خلال كتاب عنوان الدراية فيمن عرف من العلماء في المائة السابعة بيجاية لأبي العباس الغبريني - بوبرد, ابتسام (كلية الأدب العربي والفنون, 2024)
شهدت بجاية نشاطا علميا وفكريا وأدبيا بفضل اهتمام حكامها بالجانب العلمي والأدبي وتوافد العلماء من مختلف الحواضر الإسلامية حتى عدت مركز إشعاع علمي، ونشطت حركة التأليف فأثمرت مصنفات كثيرة ومنها كتب التراجم، وقد قدم أبو العباس الغبريني من خلال مؤلفه (عنوان الدراية فيمن عرف من العلماء في المائة السابعة ببجاية) صورة حقيقية للأوضاع ب بجاية لتسجيله لبعض الأحداث التاريخية و إثباته لبعض النماذج الشعرية و النثرية للأعلام المترجم لهم و حفظ لنا صورة صادقة عن الحياة العقلية ببجاية مدة قرت كامل و أظهر أثر بجاية في الح ركة الأدبية و صلاتها بمختلف حواضر المغرب الإسلامي. Bejaya witnessed scientific, intellectual and literary activity thanks to her rulers' interest in the scientific and literary side and the arrival of scientists from various Islamic cities until she returned to the center of scientific radiation, and activated The composition movement has produced many works, including scripts, and Abu al-Abbas al-Ghubrini has been introduced through his author (The title of the acquaintance is known by scholars in the seventh percent of the Bijaya) a true picture of the conditions B. Bejaya for recording some historical events and proof of some poetic and prose models of the flags translated to them and keeping us an honest picture of the mental life of Bijayah for a period of full duration and showing the impact of Bijayya in favor of the literary and its links to the various cities of the Islamic Maghreb.
Keywords: الغبريني، عنوان الدراية، الحياة الأدبية; Ghubrini, title of know-how, literary life.